La educomunicación como alternativa para visibilizar la naturalización de la violencia de género. - Armas Segarra, Daniela Michelle (2018)
Due to social constructions, men and women have been separated and hierarchized by social and human differences, man has maintained the power and control over women legitimately accepted by society, we still inherently preserve violent practices towards the feminine gender, which, many Sometimes, they can go unnoticed because they are considered natural, this continues happening every day; society is used to judge a woman but dresses, does not speak or behaves as society wants to behave, so much so that these macho practices go unnoticed, even by women themselves, so that using Educommunication is It can make these violent practices visible, since it will help to know and recognize our environment, our daily reality to achieve an active participation of society and to see violence as an existing problem, therefore this research focuses on analyze the educommunicative processes in the online course "Women's rights to a life free of violence" in which, using the observation of the same and surveys of the participants, the aim is to analyze educommunication with a tool for social change.